Future technologies for successful society development - Samoilenko, A. Y. (ТДАТУ, 2019)
Possibility of creating such technologies in the coming decades is rather uncertain. Today, primitive attempts are being made to invent something similar. And perhaps more than one century will pass before people see the finished product brought to mind, but as soon as it appears, there will be a global breakthrough in discoveries and inventions.
Keywords: neurocomputer interface; silicon microchip; Internet